Slumber Party Panic : Based on Episode#1a - Farrell, Laura (Australia Hardie Grant Egmont, 2014)
"Princess Bubblegum wants to bring all the candy people who have died back to life. But her decorpsinator serum in incomplete and the experiment goes horribly wrong. Soon the Candy Kingdom is teeming with half-dead candy people determined to feast on its sweet citizens"--Back cover.
Include illustrations
Keywords: Princesses -- Zombies